Oral and oropharyngeal high-risk HPV prevalence, HIV status, and risk behaviours in a cohort of South African men who have sex with men - Harshita B Mistry; Ramokone L Lebelo; Fulufhelo Matshonyonge; Maphoshane Nchabeleng; Matsontso Mathebula; John-Paul Bogers; Neil H Wood (AIMS Press, 2022)
Data lag is evident when observing studies focussing on human papillomavirus (HPV) prevalence in the head and neck of men who have sex with men (MSM) in Southern Africa. Sexual behaviours other than anal intercourse, and associated factors are similarly underreported. HPV vaccination has not yet commenced for this population group. One hundred and ninety-nine MSM were enrolled in this study. Participants completed a questionnaire followed by a clinical oral examination, and a rinse-and-gargle specimen in Thinprep® vials containing Preservcyt® solution was collected. Detection and genotyping for high-risk HPV were done by an automated system (Abbott® m2000sp). Six percent of MSM in this cohort had high-risk HPV present in the mouth/oropharynx. This cohort averages 29 years of age, more than half were unemployed (53.3%), and 66.8% were human immunodeficiency virus (HIV) seropositive. The most common sexual practice was anal sex (69.4%) followed by oral sex (28.6%), and by rimming (9.6%). A significant association between oral insertive sex and oral/oropharyngeal HPV status was demonstrated (p = 0.0038; phi coefficient = 0.20). An incidental but significant association between rimming and HIV status was found (p = 0.0046; phi coefficient = 0.19), and HIV seropositive participants had higher oral/oropharyngeal HPV presence. The HPV prevalence of 6% reported in this study is in alignment with global reports. The prevalence of oral/oropharyngeal HPV in this MSM cohort was influenced by sexual practices. MSM participants who practiced rimming appear to be at higher risk of HIV acquisition. Given the transmission routes of HPV in this vulnerable population, vaccination must be urgently studied as an intervention for prevention.